Diplomasi Indonesia Sebagai Negara Demokrasi Mayoritas Muslim dalam Merespon Pelanggaran HAM di Myanmar - Wahyudi, Herry; Niko, Nikodemus (POLITEA, 2023)
This research aims to analyze Indonesia's diplomacy as a majority Muslim democratic country in responding to human rights violations in Myanmar. The conflict in Myanmar, particularly concerning the treatment of the Muslim Rohingya minority, has raised international concerns. As a country with the largest Muslim population in the world and a strong democratic tradition, Indonesia plays a crucial role in responding to this situation. The research methodology employed in this study is the analysis of Indonesia's foreign policy towards Myanmar and human rights violations in that country. Data were obtained through document studies, including official government statements, political speeches, and relevant news sources. The research findings indicate that Indonesia has taken several steps in responding to human rights violations in Myanmar. The Indonesian government consistently condemns the acts of violence and human rights abuses occurring in Myanmar, including the treatment of the Rohingya. Indonesia has also utilized international forums, such as the United Nations (UN) and the Organization of Islamic Cooperation (OIC), to advocate for human rights in Myanmar. However, this research also reveals some challenges faced by Indonesia in conducting diplomacy related to Myanmar. The limited influence of Indonesia over the Myanmar government and disagreements among ASEAN member states pose constraints on Indonesia's efforts to respond to human rights violations in its neighboring country. In conclusion, Indonesia's diplomacy as a majority Muslim democratic country in responding to human rights violations in Myanmar has resulted in several constructive steps. However, the challenges encountered indicate that Indonesia's efforts still need improvement.